PENGAPLIKASIAN RUMUS HAVERSINE SEBAGAI UPAYA MENGUKUR KEKUATAN INTERAKSI ANTARWILAYAH KABUPATEN OGAN KOMERING ILIR DAN KOTA PALEMBANG - Arif Hidayat Harahap; M Iqbal Farza (Universitas Nusa Cendana, 2025)
This article uses the Haversine formula, a method of calculating the distance between two points that will be applied to the gravity model formula to show the strength of interaction between regions. In this article, the strength of inter-regional interaction that will be measured is the strength of interaction between Palembang City as the growth pole and Ogan Komering Ilir Regency, especially Kayuagung District as the hinterland of Palembang City. The purpose of this article is to combine the two theories above (Haversine formula and gravity model formula) on a real example and see the quantitative amount of interaction between the two regions, in this case the researcher took Palembang City and Ogan Komering Ilir Regency. The measurement method used is a quantitative method by measuring the value of the Harvesine formula which will be substituted into the gravity model formula with the addition of other variables, namely the population of the two regions. The results of this measurement are expected to provide a clear picture of how strong the relationship between the growth pole and hinterland.